2017
DOI: 10.1002/ecs2.1962
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and organic matter patterns in a prescribed burned and thinned managed forest ecosystem

Abstract: Citation: Owiti, D. A., I. A. Tazisong, and Z. N. Senwo. 2017. Microbial and organic matter patterns in a prescribed burned and thinned managed forest ecosystem. Ecosphere 8(12):e01962. 10. 1002/ecs2.1962 Abstract. Prescribed burning and thinning were implemented in an Alabama forest (Bankhead National Forest) as a management strategy to control pest and disease outbreaks and also to increase forest productivity. However, using fire as a control mechanism in this forest may alter soil nutrient cycling, soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
(152 reference statements)
0
1
0
Order By: Relevance
“…Pools of organic carbon in soils according to Essington (2004) Furthermore, the higher POXC content and carbon mineralization rate can be associated to the higher β-glucosidase activity which is involved in catalyzing the hydrolysis and biodegradation of plant debris. Owiti et al, (2017) showed that irrespective of treatment, xylanase activity was the highest (3244±327-5223± 567 µmol/g 24h -1 ), whereas amylase activity was the lowest (12.57± 8.9-116± 42.8 µmol/g 24h -1 ; [Fig. 14b].…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…Pools of organic carbon in soils according to Essington (2004) Furthermore, the higher POXC content and carbon mineralization rate can be associated to the higher β-glucosidase activity which is involved in catalyzing the hydrolysis and biodegradation of plant debris. Owiti et al, (2017) showed that irrespective of treatment, xylanase activity was the highest (3244±327-5223± 567 µmol/g 24h -1 ), whereas amylase activity was the lowest (12.57± 8.9-116± 42.8 µmol/g 24h -1 ; [Fig. 14b].…”
Section: Enzyme Activitiesmentioning
confidence: 99%